Pertanggungjawaban Pidana Tenaga Kesehatan Pada Pelanggaran Keamanan Data Pasien Di Era Telemedis : Analisis UU No. 17 Tahun 2023 Tentang Kesehatan - Andi Ervin Novara Jaya,; Gusti Ayu Utami, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The development of digital technology has revolutionized health service systems in many countries, including Indonesia, through the implementation of telemedicine as part of the national digital transformation agenda. Telemedicine enhances accessibility, improves service efficiency, and expands the reach of healthcare services, particularly for communities in remote regions. However, the use of digital systems in medical services also introduces serious risks concerning the security and confidentiality of highly sensitive patient data. Electronic medical records, diagnostic results, and patients’ personal information are now transmitted through electronic networks that may become targets of cyberattacks, data breaches, internal misuse, or vulnerabilities within application security systems. This study aims to analyze the criminal liability of healthcare professionals in cases of patient data breaches within telemedicine services. The research employs a normative legal method using statutory, conceptual, and comparative approaches supported by academic literature. The primary regulations examined include Law No. 17 of 2023 on Health, Law No. 27 of 2022 on Personal Data Protection (PDP), and relevant provisions of the Indonesian Criminal Code (KUHP) concerning violations of information confidentiality. The findings indicate that healthcare professionals may be held criminally liable if a data breach occurs due to intentional misconduct, gross negligence, or actions contrary to professional standards. However, within the modern telemedicine ecosystem, liability does not rest solely on individual healthcare providers; it also extends to healthcare facilities, digital platform providers, server operators, and third parties involved in data processing. This study emphasizes the need to update legal frameworks regarding the distribution of responsibilities, strengthen digital security standards, and harmonize policies between the health sector and the national cybersecurity sector.